The Feasibility of Productivity Improvement Using the Approach of Virtual Economy - Ranjbar, Samira; Maghari, Ali Esmailzadeh (International Journal of Economics and Financial Issues, 2017)
Given the crucial role of e-commerce to create knowledge-based economy, it can be called the most important context to enter the virtual economy. Increasing growth of e-commerce in developed countries and its competitive advantages as well as its important role in employment and production growth in the countries indicate that those countries have revised their current trade policies. The primary goal of this study is to investigate the relationship between productivity improvement and virtual economy. For hypotheses test, Pearson correlation coefficient and SPSS software were used. Summary and conclusion of research hypotheses suggest that there is a significant relationship between improving productivity and virtual economy, so all research hypothesis are confirmed. Keywords: productivity improvement, virtual economy, e-commerce, Pearson correlation coefficient. JEL Classifications: L81, O4